Pengaruh Lokasi, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Kacang Tanah (Studi Kasus Pada Pengusaha Kacang Tanah di Desa Kangga Kecamatan Langgudu Kabupaten Bima) - Akrabin, Akrabin; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research refers to the factors of Location, Price and Product Quality on Decisions to Buy Peanuts, with the aim of finding out whether or not an object has an influence on the subject under study. Kangga Village is a village with abundant agricultural products, one of the agricultural products in Kangga Village is peanuts. The problem most peanut producers face is price volatility. Price fluctuations are caused by an imbalance in supply and demand and are influenced by the quantity and price of production factors (inputs) used. Therefore, farmers need to know the price of peanuts, the prices of production factors, and the factors that influence changes (Achmad, 2009). Apart from that, we also strive for ideal location and product quality. The increasingly stringent role in the business world means that business actors must be smarter in understanding changes in consumer behavior. Basically, changes in consumer behavior are dynamic and very fast. Keywords : Influence of Location, Price and Product Quality